The effects of Stevia rebaudiana consumption on male reproductive parameters: a cross-sectional study - Oliwi, Abdelhameed Abdelkhaliq; Al-Hamdani, Hussein Ali; Khalifa, Abdulrhman Y.; Abed, Hayder H.; Hussein, Tamara Ala’a; Salihi, Karima A. Al (Pharmakeftiki, 2025)
Stevia, a natural sweetener deriving from the leaves of the plant Stevia rebaudiana, has gained widespread popularity as a sugar substitute. This study aimed at evaluating the effects of stevia consumption on male reproductive parameters, with particular emphasis on serum testosterone concentration and sperm count. A cross-sectional study was conducted in Samawah City, Iraq, between February 2023 and April 2024, involving 80 male participants. Subjects were categorized into two groups: a stevia-treated group (N=40), which consumed stevia as a dietary sugar substitute, and a control group (N=40), which maintained their habitual dietary intake. Serum testosterone levels (µg/L) and semen samples were analysed in order to assess reproductive parameters, including sperm count (×106/mL), sperm motility (%), and sperm morphology. The mean age of participants did not differ significantly between the control group (33.65 ± 7.16 years) and the stevia-treated group (35.95 ± 5.72 years). Stevia consumption had no statistically significant effect on serum testosterone levels, with mean values of 21.10 ± 11.84 µg/L in the control group and 20.03 ± 10.84 µg/L in the stevia-treated group. Although a non-significant increase in sperm morphological abnormalities was observed in the stevia-treated group, sperm motility remained unaffected. Notably, a statistically significant reduction in sperm count was detected in the stevia-treated group (18.03 ± 8.938 ×10⁶/mL) compared to controls. In conclusion, dietary stevia intake did not alter serum testosterone levels or sperm motility. However, it was associated with a significant decrease in sperm count and a slight, non-significant increase in sperm deformities.